(3GdOQI Ydi dSGf GdTjN CHj eSQI Edi ENhGfg ef GdeLHQIs - (3GdMGce CHj SYO GdMSf Hf cQGeI GdLTej GdHjgbj GdHQhbj,J (B494 (3g` s ((3eMeO Hf CMeO s)
(3ChdgG (B:s
(3GdHGH GdChd , ajeG UOQJg GdQSGdI ef GdScGf ef GdYOdjI s
(3BNQgG (B:s
(3hPdc SQ YXje , hNWH LSje Je GdcJGH HYhf Gddg GdYRjR GdQMje hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdQSGdI ai (B16 (3HGHkGs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B289s
Keywords: (3GdJhMjO hGdedd hGdfMds